Cultivating Independent Character in Students at the Cendekia Berseri School in Makassar City - Nurul Indah Ramadani; Muqimah Surganingsih; Nur Nabila Binti Mohd Rafee (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
The world of education has three domains that students must master: cognitive, affective, and psychomotor. The cognitive domain is oriented toward mastery of science and technology, and the affective domain is related to attitude, morality, spirit, and character. In contrast, the psychomotor domain is linked to procedural skills and tends to be mechanical. However, in the reality of learning in schools, efforts are always made to balance these three domains, but in fact, the dominant domain is the cognitive and then psychomotor domains; the result is that students are rich in hard skills but lacking in soft skills because the affective domain is ignored. The speed of technology and the rapid development of the times require people with character who can adapt to their environment and keep up with technological growth. For this reason, character strengthening and education are essential. Researchers use this type of qualitative research because qualitative research requires data and information in the form of descriptions and narratives to reveal the meaning behind the informants' descriptions/descriptions. A child's character will be formed from the habits they get at school and home. Therefore, good cooperation between teachers and parents is needed so that interpretation can occur between the habits made by teachers and parents.